ALTERNATIF PONDASI TEROWONGAN LAYANG DALAM LAUT UNTUK PRASARANA TRANSPORTASI - Aspar, Wimpie Agoeng N.; Prijo Utomo, Djoko; Hendriyawan, Hendriyawan (Badan Pengkajian dan Penerapan Teknologi, 2010)
A Submerged Floating Tunnel (SFT) is a tunnel that floats in water, supported by its buoyancy specifically by employing the hydrostatic thrust. In order to construct the foundation of the SFT, soil investigation has to be performed in advance. The soil investigation includes identification of subsurface soil profile, geotechnical index properties and parameters. Results of the soil investigation were used to he analyze and develop alternatives of the foundations for anchoring the prototype of the SFT. This paper discusses the alternatives of the foundations based on soil condition and applied tension leg. The research will be of interest to many practicing engineers and researchers regarding the subject matter.